Beyond Flexner: A New Model for Continuous Learning in the Health Professions - Bonnie M. Miller; Donald E. Moore; William W. Stead; Jeffrey R. Balser (2010)
One hundred years after Flexner wrote his report for the Carnegie Foundation, calls are heard for another "Flexnerian revolution," a reform movement that would overhaul an approach to medical education that is criticized for its expense and inefficiency, its failure to respond to the health needs of our communities, and the high cost and inefficiency of the health care system it supports. To address these concerns, a group of Vanderbilt educators, national experts, administrators, residents, and students attended a retreat in November 2008. The goal of this meeting was to craft a new vision of physician learning based on the continuous development and assessment of competencies needed for effective and compassionate care under challenging circumstances. The vision that emerged from this gathering was that of a health care workforce comprised of physicians and other professionals, all capable of assessing practice outcomes, identifying learning needs, and engaging in continuous learning to achieve the best care for their patients. Several principles form the foundation for this vision. Learning should be competency based and embedded in the workplace. It should be linked to patient needs and undertaken by individual providers, by teams, and by institutions. Health professionals should be trained in this new model from the start of the educational experience, leading to true interprofessional education, with shared facilities and the same basic coursework. Multiple entry and exit points would provide flexibility and would allow health professionals to redirect their careers as their goals evolved. This article provides a detailed account of the model developed at the retreat and the obstacles that might be encountered in attempting to implement it.